Communicating Heritage: Public Relations Strategies of Historical Hotels in East Java - Hilda Yunita Wono; Zinggara Hidayat; Burhan Bungin (Mediator: Jurnal Komunikasi, 2025)
Heritage communication in the hospitality sector plays a crucial role in preserving cultural identity while enhancing destination branding. Despite the growing popularity of heritage tourism, research on heritage-based public relations (PR) strategies in Southeast Asia—particularly in postcolonial settings like Indonesia—remains limited. This study investigates how five historic hotels in East Java communicate their cultural and historical narratives through PR strategies that connect with both domestic and international visitors. Adopting a qualitative multi-case study, the research combines in-depth interviews, participant observation, and document analysis. The findings highlight three distinctive narrative orientations—nationalist, local-cultural, and colonial-aesthetic—delivered through PR models ranging from traditional information dissemination to participatory engagement. Digital storytelling emerges as a central mechanism for amplifying heritage branding and shaping public perception. This study positions heritage PR as an interdisciplinary field bridging communication, tourism, and cultural preservation, while offering practical insights for hotels to strengthen storytelling practices and collaborate more closely with local communities.